Strength & conditioning: Principles for track and field athletes - Cissik, J. M. (Modern Athlete & Coach, 2014)
The article offers the author's view on strength, conditioning, and speed training for track and field athletes. He outlines five principles of using strength training for track and field athletes. He mentions that strength training must support and complement Track and Field training. He adds that the strength and power of track and field athletes must be developed every year to enhance their training skills.